HASIL RATUN PERTAMA BEBERAPA VARIETAS SORGUM (Sorghum bicolor (L.) Moench) DENGAN PERBEDAAN FASE PERATUNAN - Nurhaliza, Evi; Zubaidi, Akhmad; Anugrahwati, Dwi Ratna (Fakultas Pertanian, Universitas Janabadra, 2024)
This research aims to evaluate the first ratoon yield of several sorghum varieties with different ratooning times. This research was carried out in the Greenhouse of the Faculty of Agriculture, Mataram University from August to December 2023. The design used in this research was a factorial completely randomized design (CRD) with two factors studied, namely plant variety and ratoon phase. The plant varieties used are Bioguma, Gando Keta, Super 2, Suri 4. Ratooning was carried out on 3 different phases of the main plant which are flag leaf, flowering, and harvest phase. The results showed that the Gando Keta variety had the highest number of seeds and seed weight. The highest 100 seed weight was shown by Suri 4 and Super 2, while the highest dry matter weight was found in Beoguma and Super 2 varieties. The highest number of seeds, seed weight, and 100 seed weight were shown by flag leaf phase ratooning, while the highest dry grain weight was shown in the harvest time ratooning. The highest dry grain weight was obtained in the Bioguma variety with harvest time ratooning, while the highest yield (seed weight) was obtained by Gando Keta at the flag leaf phase ratooning.